2009
DOI: 10.1007/s12665-009-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the acidic potential of waste rock in the Akara gold mine, Thailand

Abstract: Acid mine drainage (AMD) is the environmental issue that generates the greatest public concern regarding the mining industry. Thus, characterization of mine waste rock according to acid generation potential is necessary for mining operations to ensure proper waste rock storage and to avoid future adverse environmental effects. Therefore, this study was conducted to estimate the potential of AMD generation in the largest operating gold mine in Thailand by using acid base accounting and net acid generation tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…It is also noticed that the hanging wall zone consisting of lithic-rich fiamme breccia is considered a permeable rock, which can have board zones of hydrothermal alteration [6]. The result of this study is consistent with the data in Changul et al [14], who reported that PAF materials are identified in the silicified lapilli tuff and sheared tuff units in the C-H pit (H ore lens is a part of the C-H pit) at the Chatree mine. As the tuff units are indicated to occur in the northwestern part of the C-H pit, which corresponds to the distribution of the lithic-rich fiamme breccia unit in the hanging wall zone, the tuff units classified as PAF in Changul et al [14] are equivalent to the PAF rocks characterized in this study.…”
Section: Acid Rock Drainage Potentialsupporting
confidence: 90%
See 3 more Smart Citations
“…It is also noticed that the hanging wall zone consisting of lithic-rich fiamme breccia is considered a permeable rock, which can have board zones of hydrothermal alteration [6]. The result of this study is consistent with the data in Changul et al [14], who reported that PAF materials are identified in the silicified lapilli tuff and sheared tuff units in the C-H pit (H ore lens is a part of the C-H pit) at the Chatree mine. As the tuff units are indicated to occur in the northwestern part of the C-H pit, which corresponds to the distribution of the lithic-rich fiamme breccia unit in the hanging wall zone, the tuff units classified as PAF in Changul et al [14] are equivalent to the PAF rocks characterized in this study.…”
Section: Acid Rock Drainage Potentialsupporting
confidence: 90%
“…Several published papers assess the environmental aspects of the Chatree mine [8,13,14,16,17,47], and these studies discuss and conclude a wide range of potential environmental issues at the Chatree, including potential AMD generation in the future. However, the data produced in previous studies are based principally on samples collected either from the waste dump or tailing sites where mixed materials are stored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABA is claimed as the first technology available to predict the quantity of acid-producing materials prior to mining. With the enactment of the Surface Mining Control and Reclamation Act of 1977 (SMCRA) in the USA, ABA in 1977 and the 8 th International Conference on Acid Rock Drainage, International Network for Acid Prevention, June 2009, Skelleftea, Sweden, ABA has become widely adopted as a method to predict post-mining drainage quality through overburden chemistry analysis 6,7 ABA tests quantify the balance net acid producing potential (NAPP) between potentially acidgenerating potential (MPA), particularly the oxidation of sulfide materials, and acid neutralizing capacity (ANC) in a sample, such as the dissolution of alkaline, carbonates, displacement of exchangeable bases and weathering of silicate 8,9 . The ABA parameters are described below: a.…”
Section: Acid-base Accounting (Aba)mentioning
confidence: 99%